Determinanty efektywności systemu CAE w procesie edukacji dzieci z utrudnieniami w rozwoju - Krauze-Sikorska, Hanna (Wydawnictwo Naukowe UAM, 2012)
It has changed not only the situation of the contemporary child with developmental diffi culties but also its education. PCs, laptops, tablets, and smartphones with their multimedia features have become an integral element of the child’s world and an inseparable part of education. In the article the author refers to quasi-experimental research results, which indicate the use of technology in computer-assisted education that takes into consideration the fact that the child does not have at its disposal neither “IT maturity” nor “information maturity”. The role of a teacher as a tutor and facilitator is very important. The process of using CAE in educating children with developmental diffi culties needs to be thought out beforehand, using “joint involvement episodes” and “scenes of joint attention” to create a coherent triad: child – computer – teacher so that the child could understand the aim and sense of the activity performed. Unfortunately, the possibility of using CAE is often restricted by the teachers’ lack of competences, not only technical, but concerning the necessity of finding an appropriate, customised educational path for each and every child.
Determinants of the Effectiveness of CAE in the Process
Keywords: CAE (Computer Assisted Education); children with developmental difficulties; personalization; Children with developmental difficulties; personalization